Determination of material parameters from regions close to the collector using electron beam-induced current - Wu, Dethau. (2009)
The conventional method of extracting the minority carrier diffusion length using the electron beam-induced current (EBIC) technique requires that the electron beam be placed at region more than two diffusion lengths away from the collector. The EBIC signals obtained under this condition usually has low signal to noise ratio. In addition, the true diffusion length of the sample is initially unknown and hence it is difficult to estimate how close the beam can be placed from the collector. To overcome all these difficulties, a new method of extracting minority carrier diffusion length from the EBIC signal is proposed. It is shown that this method can be applied to EBIC signals obtained from regions close to the collector. It is also shown that the surface recombination velocity of the sample can also be obtained using this method. This theory is verified using EBIC data generated from a device simulation software.